UJI AKTIVITAS ANTIDIARE EKSTRAK ETANOL 70% KULIT BUAH JENGKOL (Archidendron pauciflorum (Benth.) I.C.Nielsen) TERHADAP MENCIT JANTAN YANG DIINDUKSI OLEUM RICINI - Mohammad Rizal; Yusransyah Yusransyah; Sofi Nurmay Stiani (Jurnal Ilmiah Manuntung, 2016)
Plants that can be used as a medicinal plant one of which is Jengkol (Archidendron pauciflorum (Benth.) IC.Nielsen.). Seeds, bark and leaves jengkol contains saponins, flavonoids and tannins. The purpose of this study was to test the antidiarrheal activity of 70% ethanol extract of the fruit peel jengkol (Archidendron pauciflorum (Benth.) ICNielsen) to male mice that includes a solution of distilled water as a control, loperamide as a comparison, the ethanol extract of the fruit peel jengkol as test material, and oleum ricini as inductors. Research method used laboratory experiments. Data were analyzed by ANOVA (Analysis of Variance) and continued with different test average – average Duncan using SPSS (Statistical Product and Service Solutions). The results of that study 70% ethanol extract of the fruit peel jengkol (Archidendron pauciflorum (Benth.) IC Nielsen) provide nonspecific antidiarrheal activity. The content of the metabolites were present in 70% ethanol extract of the fruit peel jengkol (Archidendron pauciflorum (Benth.) IC Nielsen) which provides non-specific activity as antidiarrheal are tannins, flavonoids and steroids. Ethanol Extract Fruit Leather Jengkol 1.2 mg / g has a stronger effect in reducing diarrhea and provide optimum activity as nonspecific antidiarrheal.